Regional order in South Asia: Sine Qua Non for Indian foreign policy - Hossain, Ishtiaq (East-West Publishing Co. Ltd. Oneonta, New York, USA, 1991)
In this paper, first of all, the regional order in South Asia will be defined. Then an attempt will be made to identify the key elements of that order. A number of factors may challenge that order. These are also to be analyzed. Finally, the main arguments of the paper will be summarized in a conclusion.